Modelagem da disponibilidade hídrica em refinarias de petróleo brasileiras : o caso da REPLAN - Souza, Leticia Magalar Martins de (2018)
Water is an essential resource for the production of derivatives, but increasingly scarce. In Brazil, in cases of water shortages, human and animal supplies are prioritized, which directly affects the industrial sector. In this context, the present study aims to analyze to what extent the multiple uses of water in a region can affect the operation of refineries and indicate possible alternatives to reduce water consumption. To this end, the production of the Brazilian refining plant was simulated to obtain its water demand through the tool Carbon and Energy Strategy Analysis for Refineries (CAESAR). Next, the region in which each refinery is located was classified in relation to the availability of water through two indicators and a refinery was chosen in a critical location for a case study. This consists in the elaboration of a water balance of the hydrographic region that the refinery is inserted considering other consumptive uses during the period between 2015 and 2040 with the aid of the Water Evaluation and Planning (WEAP) tool. The refinery chosen was REPLAN and the results obtained indicate the possibility of future water restriction due to the conflict of multiple water uses in the analyzed region. Finally, it is suggested possible ways of minimizing the water consumption of oil refineries..